2017
DOI: 10.1016/j.ecoleng.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

How do root and soil characteristics affect the erosion-reducing potential of plant species?

Abstract: Plant roots can be very effective in stabilizing the soil against concentrated flow erosion. So far, most research on the erosion-reducing potential of plant roots was conducted on loamy soils. However susceptible to incisive erosion processes, at present, no research exists on the effectiveness of plant roots in reducing concentrated flow erosion rates in sandy soils. Therefore, the prime objective of this study was to assess the erosion-reducing potential of both fibrous and tap roots in sandy soils. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…Similar to soil erodibility studies, research dealing with effects of plant roots on soil detachment rates has mainly focused on silt loam soils whereas these effects in sandy and clayey soils are less well understood (Vannoppen et al, 2015). For instance, Vannoppen et al, 2017 demonstrated that the erosion-reducing effects of fibrous and tap roots during concentrated runoff on sandy soils are different from those observed in loamy soils. In loose sandy soils, fibrous roots seem to be more effective in reducing erosion rates whereas tap roots seem to be much less effective as compared to the effects of these root properties in loamy soils.…”
Section: Vegetationmentioning
confidence: 99%
“…Similar to soil erodibility studies, research dealing with effects of plant roots on soil detachment rates has mainly focused on silt loam soils whereas these effects in sandy and clayey soils are less well understood (Vannoppen et al, 2015). For instance, Vannoppen et al, 2017 demonstrated that the erosion-reducing effects of fibrous and tap roots during concentrated runoff on sandy soils are different from those observed in loamy soils. In loose sandy soils, fibrous roots seem to be more effective in reducing erosion rates whereas tap roots seem to be much less effective as compared to the effects of these root properties in loamy soils.…”
Section: Vegetationmentioning
confidence: 99%
“…The effect of root reinforcement increases the cohesive strength of soil, decreases soil deformation, prevents the incidence of surface tension cracks, and can avoid slope failure initiated by triggering factors [6][7][8][9][10][11][12][13][14][15][16]. The shear stress is developed in the soil and transferred to the ground as tensile resistance in the roots, which ensures mechanical reinforcement by the roots [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[Colour figure can be viewed at wileyonlinelibrary.com] GULLY SEDIMENT YIELD REDUCTIONS FOLLOWING REHABILITATION the walls and floor) for maximum stabilization (Wilkinson et al, 2018). The functional attributes (such as root length, density and architecture) of the vegetation species, both above and below ground, are also important for facilitating infiltration and reducing runoff and erosion above and within gullies (Gyssels et al, 2002(Gyssels et al, , 2005De Baets et al, 2009;Stokes et al, 2014;Vannoppen et al, 2017).…”
mentioning
confidence: 99%